Simulated Warming Reduces Biomass Accumulation in Zizania caduciflor and Sparganium stoloniferum - Tingfeng Wang; Junbao Yu; Yun Zhang; Kun Tian; Xiangyu Zhu; Mei Sun; Zhenya Liu (Plants)
Climate change, represented by global warming, significantly affects the structure and function of alpine wetland ecosystems. Investigating the response strategies of alpine wetland plants to temperature changes is fundamental to understanding how alpine wetlands cope with global warming. This study, conducted at the typical alpine wetland Napahai, uses the latest predictions from the Intergovernmental Panel on Climate Change (IPCC) and employs open–top chamber warming experiments (OTCs) to study the responses of typical alpine wetland plants, Zizania caduciflor and Sparganium stoloniferum, to simulated warming. The results indicate that simulated warming significantly reduced the photosynthetic capacity of Z. caduciflor, and obviously decreased the biomass accumulation of both Z. caduciflor and S. stoloniferum (p < 0.05). The mean annual temperature (MAT) and annual maximum temperature (max) are the primary temperature factors affecting the photosynthetic and biomass parameters. Specifically, the net photosynthetic rate, stomatal conductance, transpiration rate, the aboveground, underground, and total biomasses, and the nitrogen contents of aboveground and underground buds of Z. caduciflor all showed significant negative correlations with MAT and max (p < 0.05). The parameters of S. stoloniferum mainly showed significant correlations with max, with its underground biomass, total biomass, and root nitrogen content all showing significant negative correlations with max, while its fibrous root carbon content and underground bud phosphorus content showed significant positive correlations with max (p < 0.05). The results are consistent with previous studies in high–altitude regions, indicating that warming reduces the photosynthetic capacity and biomass accumulation of alpine wetland plants, a trend that is widespread and will lead to a decline in the productivity of alpine wetlands and changes in vegetation composition. The study can provide a case for understanding the response strategies of alpine wetlands in the context of climate change.